Tools Used in Modeling of the Economic Processes - Pompiliu Cristescu, Marian (KnE Social Sciences, 2020)
The paper aims at identifying the economic process modeling languages, starting from the premise that the main beneficiaries of the resulting models are economists or decision-makers, respectively economic researchers. There are a large number of languages that have been developed with different objectives, but they have all been used to describe business processes. Languages have studied different aspects of business processes (dynamic, functional, organizational, informational) and may be more or less formal, depending on the intended use and audience. There is no easy way to classify these languages along a single dimension. However, the languages fall into four groups, clearly defined scientifically or professionally: traditional process modeling languages, object-oriented languages, dynamic process modeling languages, and the integration of languages. Economic processes are generally very complex and, therefore, different points can be formulated about their modeling. Keywords: Formal language, model, simulation, algorithm, business processes.